Análisis comparativo entre los métodos de autenticación unifactorial y multifactorial - Valverde Castro, Jonathan David (2023)
In today's digital age, information security is of paramount importance. Authentication plays a vital role in ensuring exclusive access to sensitive systems, applications and data. This study focuses on comparing two authentication methods: single-factor and multi-factor. Single-factor authentication relies on verifying a single element, such as a password or fingerprint. In contrast, multifactor authentication involves evidence such as what the user knows (password), what the user has (security token) and who This study adopted a deductive approach and employed user surveys as part of the research process. The main objective is to perform a detailed comparative analysis of single-factor and multifactor authentication methods, evaluating their security and usability. It aims to identify the strengths and weaknesses of each approach, providing a clearer picture of when and how each approach can be effectively implemented. Given the increase in cyberattacks and security breaches, multifactor authentication is becoming a more robust option for protecting user identities. This comparative analysis helps to better understand which approach is best suited to specific needs and how to leverage its benefits in today's digital environment. is the user (fingerprint or facial recognition).